2015
DOI: 10.1071/he14069
|View full text |Cite
|
Sign up to set email alerts
|

‘The secret shame’: a content analysis of online news reporting of a celebrity admitting smoking while pregnant

Abstract: Issue addressed: Around one in 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…14,[19][20][21][22][23] The aim of this research was to identify the extent and nature of online news readers' reactions to online news items that reported the 'Swan pregnant and admitting smoking' announcement and whether these comments provide any health information about the harms of smoking during pregnancy. Previous research relating to this celebrity news story 9 showed that the media coverage focused on whether Swan or other women should be judged for smoking when pregnant. This study examines the arguments shared by online news readers that either supported or opposed this judgement.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…14,[19][20][21][22][23] The aim of this research was to identify the extent and nature of online news readers' reactions to online news items that reported the 'Swan pregnant and admitting smoking' announcement and whether these comments provide any health information about the harms of smoking during pregnancy. Previous research relating to this celebrity news story 9 showed that the media coverage focused on whether Swan or other women should be judged for smoking when pregnant. This study examines the arguments shared by online news readers that either supported or opposed this judgement.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis also noted a lack of information encouraging and supporting pregnant women to quit smoking. 9 Studies of the impact of celebrity health stories have reported improvements in health behaviours such as cancer screening and information seeking. 10,11 However, any important, factual health information reported in these newsworthy 'human interest' storylines tends to be overshadowed by the celebrity-focused content, suggesting missed opportunities for public health practitioners to use these stories as a communication opportunity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations